The relevance of Psalm 23 for people after natural disasters in Central Sulawesi - Nole, Otniel Aurelius (Institut Agama Kristen Negeri Toraja, 2024)
Human life moves forward, but no one knows for sure. Likewise, the people never realized that they would experience the events of September 28, 2018, in Central Sulawesi. These events are cases of three types of natural disasters: earthquakes, tsunamis, and liquefaction. These natural disasters caused significant suffering to them. Nevertheless, the memoirs about this incident reminded them of God’s nature and attitude as a faithful shepherd, as expressed in the faith of Psalm 23. This research aims to analyze the relevance of Psalm 23 for people after natural disasters in Central Sulawesi. This research used a qualitative method that involved data collection through observation, interviews, and a survey with a questionnaire. The researcher found that natural disasters made them suffer from fear, loss, and anxiety, but God’s providence was always evident for them to bounce back. Psalm 23 was relevant to people’s experiences after natural disasters in Central Sulawesi. That can be seen from the awareness of God’s grace, which continues to care for them. Efforts to survive, recover, and develop are concrete manifestations of God’s help for them. The common point between the Psalmist in Psalm 23 and the survivors of the Central Sulawesi natural disasters are existential experiences of God’s existence.